Computerisation of primary care in Wales. Issue 6794 (13th July 1991) - Goves, J R; Davies, T; Reilly, T
Abstract : OBJECTIVE–To obtain information about the computerisation of general practice in Wales, and to enable more effective planning of educational provision for doctors and other primary health care workers. DESIGN–Postal questionnaire sent to all general practices in Wales. SUBJECTS–553 general practices, of which 401 (73% replied). RESULTS–The level of computerisation varied from 11 (85%) of practices in Powys Family Health Services Authority to 22 (40%) in Mid Glamorgan. Less than half of practices had a computer in only two authorities. The commonest uses of the computer were for patient registration (208 practices), repeat prescribing (180), call and recall of patients (165), and partial clinical records (122). The main suppliers were VAMP (78 practices), AAH Meditel (46), and AMC (23). 102 of 226 practices with a computer had a terminal on each doctor's desk. Just 33 practices had full patient notes on computer and 51 had modems for electronic communication. CONCLUSION–Mechanisms to encourage greater and more sophisticated use of computers and information technology need to be explored.